Open Access and Article Processing Charges with Special Reference to Indian Institutions: Analyzing Fee Waivers, Discounts, and Transformative Agreements - Alam, Md Nurul; Das, Anup Kumar (Journal of Data Science, Informetrics, and Citation Studies)
The shift from traditional subscription-based publishing to Open Access (OA) has transformed scholarly communication by providing unrestricted access to research outputs, fostering global knowledge exchange. However, the rise of Article Processing Charges (APCs) levied by publishers to cover operational costs in the OA model poses significant challenges, particularly for researchers from lower-middle-income countries like India. This study investigates the interplay between OA and APCs, focusing on the Indian academic and research landscape. It evaluates the effectiveness of mechanisms such as fee waivers, discounts, and transformative agreements in alleviating the financial burden of APCs and enabling equitable access to OA publishing. This research aims to examine current trends in OA adoption in India, identify barriers to participation in APC-based publishing, and propose solutions for Indian researchers to increase access to OA. This study incorporates an approach which is a combination of exhaustive literature review, global and national OA policies analysis, and case studies from Indian institutions that have successfully negotiated agreements with publishers. Key findings highlight the disparities in APC costs across disciplines and publishers, with fees ranging from $8 to USD 5,000. While fee waivers and discounts are available, their effectiveness is limited by cumbersome application processes and a lack of awareness among eligible researchers. Transformative agreements, wherein institutions negotiate lump-sum payments to cover subscription and OA publishing costs, emerge as a promising solution but remain in their infancy in India. The study also underscores the role of government and institutional policies in promoting OA publishing. Initiatives like the "One Nation One Subscription" (ONOS) policy and developing a national Green OA repository represent positive steps. However, significant gaps remain in addressing funding challenges and ensuring the widespread adoption of OA practices. Case studies of Indian institutions, such as the Indian Institute of Science (IISc) and the Institute of Plasma Research (IPR), demonstrate the potential of negotiated agreements to reduce APC costs and increase OA publications. However, these agreements often have limited scope and require greater coordination between institutions, publishers, and policymakers. The study concludes that while OA presents significant opportunities for democratizing access to knowledge, the financial burden of APCs remains a critical barrier for Indian researchers. A multifaceted approach is essential to address these challenges, including developing a comprehensive national OA policy, increased institutional support for APC funding, wider adoption of transformative agreements, and enhanced awareness of alternative OA models such as Diamond and Platinum OA. By implementing these strategies, India can strengthen its position in the global OA landscape, ensuring its researchers have equitable access to publish and disseminate their work. This research contributes to the on-going discourse on OA publishing, offering actionable insights for policymakers, institutions, and researchers striving to create a more inclusive and sustainable academic publishing ecosystem.
Keywords: Article Processing Charges; APCs; Open Access; Gold Open Access; Fee Waiver; Transformative Agreement; ONOS; India.